Every landlord's guide to finding great tenants - Portman, Janet; O'Connell, Ann (Ann Kristin), 1979- (Berkeley, California : NOLO, 2020)
"This book guides landlords through the process of attracting and screening potential tenants, and explains how to avoid problem tenants. It covers how to avoid discrimination complaints, advertise effectively, screen tenants over the phone, show the unit, evaluate applications, examine credit reports, check references, make a rental offer, and reject applicants"--
Choosing good tenants makes good business sense -- Complying with discrimination laws -- How to deal with current tenants -- before you look for new ones -- How to advertise effectively -- How should you show your rental? -- Preparing your rental application and screening materials -- Fielding initial questions and phone screening -- Prepare your rental for an open house or showing -- Face to face : showing the rental and negotiating with prospective tenants -- Evaluating rental applications -- Checking applicants' credit reports -- Checking landlord, employer, and personal references -- Checking applicants' criminal backgrounds -- How to choose and work with a tenant-screening agency -- Choosing your new tenant -- How to reject -- what to say, what to write.
Includes index (pages 444-458).
"With downloadable forms" --Cover.
"Advertise legally, effectively, and clearly - Evaluate credit reports, background reports, and references - Avoid fair housing mistakes" --Cover.
"Free legal updates at nolo.com" --Cover.
110593
Keywords: Landlord and tenant -- United States -- Popular works; Rental housing -- United States -- Popular works; Landlords -- United States -- Handbooks, manuals, etc; Handbooks and manuals; Popular works